A Comparison of Digital Reading Behaviors Among Graduate Students in Taiwan and The USA - Lin, Suyu; Chen, Chia-Hsiang; Ke, Hao-Ren (International Journal of Informatics and Information Systems, 2021)
This is a comparative study on digital reading behaviors between students in Graduate Institute of Library and Information Studies (GLIS) in National Taiwan Normal University and School of Information Studies (SOIS) in University of Wisconsin-Milwaukee. By making a connection between their habits and various forms of capital that may shape their reading behaviors, this study adopts a qualitative approach to focus on the four key concepts of Bourdieu’s practice theory: habitus, economic capital, cultural capital, and social capital to analyze the factors that influence digital-reading behaviors. The results indicate that the graduate students' digital reading behavior is influenced mostly by their family, school and library. Graduate students like to use electronic resources (online database and the Internet) to conduct academic research and still prefer print textbooks. When comes to digital reading, in GLIS, students with more than two digital reading devices tend to get free digital contents from various sources. However, in SOIS, students with more than one digital reading service tend to purchase digital contents from the Internet. Graduate students’ reading behaviours might be influenced by their economic capital.